Respuesta :

Multiply the first equation in    y + 3x = -1 and 2y - 5x =31     by -2, to obtain:

-2(y + 3x = -1)     =>  -2y - 6x = +4
                                   2y        =    5x + 31   (this is the 2nd equation)
                                 ___________________
                                        -6x  = 5x + 35, or -11x = 35, or x = -35/11

Subst.  -35/11 for x in either of the given equations, to find the value of y.

Then write y our solution in the form (-35/11,   ?    ).

As always, you should check your answer.